Semiconductor packaging : materials interaction and reliability - Chen, Andrea (CRC Press, 2012)
"In semiconductor manufacturing, understanding how various materials behave and interact is critical to making a reliable and robust semiconductor package. Semiconductor Packaging: Materials Interaction and Reliability provides a fundamental understanding of the underlying physical properties of the materials used in a semiconductor package. The book focuses on an important step in semiconductor manufacturing package assembly and testing. It covers the basics of material properties and explains how to determine which behaviors are important to package performance. The authors also discuss how the properties of packaging materials interact with each another and explore how to maximize the performance of these materials in regard to package integrity and reliability. By tying together the disparate elements essential to a semiconductor package, this easy-to-read book shows how all the parts fit and work together to provide durable protection for the integrated circuit chip within as well as a means for the chip to communicate with the outside world"--